THE INFLUENCE OF JOB SATISFACTION AND WORK CLIMATEON WORK SPIRIT IN THE OFFICEMEDAN CITY COOPERATIVE AND UMKM SERVICE - Salmon (Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to determine the effect of Job Satisfaction and Work Climate on Work Enthusiasm at the Medan City Umkm Cooperative Service. The test method used is sampling testing, the number of tests in this review is 35 respondents taken from the population. seen from the F test obtained Tcount 14.405 > Ftable 3.285 with sig 0.000 <α 0.05, indicating that H0 is rejected and H1 is recognized, which means job satisfaction and work climate together have a significant effect on the variable morale. Judging from the results of the t test, it is very clear that the tcount of the morale variable is 3.181 greater than the Ftable of 1.692 with a possible t of 0.003 which means it is more significant by 0.05 on the morale variable. the variable of job satisfaction is seen from the variable of work enthusiasm. on the work climate variable, a tcount of 4.363 is greater than a ttable of 1.692 with a probability of sig 0.000 which is imperfect with the furthest level of importance reaching 0.05, so that the work climate variable is more or less visible than the work spirit variable. The Adjusted R Square value obtained means 0.441, this figure indicates that 44.1% of morale (reliable variable) can be explained by job satisfaction and work climate.